Long-term monitoring of a winter bat assemblage revealed large fluctuations and trends in species abundance - Rafał Bernard; Radosław Jaros; Juliusz Samoląg; Jakub Z. Kosicki (European Journal of Ecology, 2020)
Monitoring studies in Strzaliny, one of the greatest hibernacula in Poland, comprised 31 annual bat censuses (1989–2019). The abundance peaked in 2002 for Myotis myotis, 2009 for Myotis nattereri and 2008 for the whole assemblage. Comparison of the maximum abundance in the monitoring period with that from 1980 to 1982 showed an almost fourfold increase for the whole assemblage, tenfold increase for M. nattereri and fourfold increase for M. myotis.